E-COMMERCE KEPADA UMKM MINIATUR KAPAL UNTUK MENINGKATKAN DAYA SAING DI ERA GLOBAL - Mu’azamsyah, Muhammad; Fatahuddin, Fatahuddin; Muqtafin, Muqtafin; Armanda, Erwin; Nadia, Nadia; Masyita, Nita Nur; Tambunan, Rudi; Silvia, Silvia (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
The problem faced by Pengudang Village when we conducted the survey was that the community still lacked knowledge and training related to social media as a business promotion tool. This is due to the location of Pengudang Village which is far from the city center and there are no facilities or staff to provide outreach to the community regarding the digital era for promotion. We see that the potentials of Pengudang Village have not been maximized properly. Therefore, we provide training and marketing assistance through e-commerce to MSMEs Miniature Pinisi Ships which aim to boost the MSME economy again. We focus on marketing through e-commerce for MSMEs Miniature Pinisi Ships through social media Instagram, Facebook and WhatsApp by creating a new Instagram account for the business and tidying up the business owner's Facebook account while WhatsApp still uses the business owner's personal account. The marketing steps through social media are by posting photos of the business product in the form of Miniature Pinisi Ships on the social media accounts mentioned above as well as describing the method of manufacture and materials used to make products and procedures for ordering or purchasing Miniature Pinisi Ships